2001
DOI: 10.1054/bjoc.2001.1913
|View full text |Cite
|
Sign up to set email alerts
|

Topographic analysis of K-ras mutations in histologically normal lung tissues and tumours of lung cancer patients

Abstract: Mutations in the K-ras gene are very common in lung tumours and are implicated in the development of lung cancer, but the timing of their occurrence remains poorly understood. We investigated K-ras mutations in cell samples microdissected by laser capture microscopy at multiple sites from lung tissue sections representing tumour tissue and matched histologically normal tissue obtained from 48 lung cancer patients. K-ras mutations were detected in cell samples from 10 of 38 (26.3%) lung adenocarcinomas and in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Because chronic inflammation may be present in patients without cancer as well as those with cancer (9 ), the analysis of K-ras mutations in plasma may be influenced by such factors. Finally, as reported recently by Keohavong et al (10 ), K-ras mutations are frequently found in histologically normal tissues near tumors, suggesting that such mutations may represent an early event in the development of lung cancer. K-ras mutations thus may be present before clinically detectable tumors.…”
Section: To the Editorsupporting
confidence: 70%
“…Because chronic inflammation may be present in patients without cancer as well as those with cancer (9 ), the analysis of K-ras mutations in plasma may be influenced by such factors. Finally, as reported recently by Keohavong et al (10 ), K-ras mutations are frequently found in histologically normal tissues near tumors, suggesting that such mutations may represent an early event in the development of lung cancer. K-ras mutations thus may be present before clinically detectable tumors.…”
Section: To the Editorsupporting
confidence: 70%
“…These findings have other important clinical implications. They also suggest that the use of RAF inhibitors might be pointless and even deleterious in normal tissues especially in cells harboring a RAS mutation, as it can be found in lung and colon tissue, for example (40,41). Indeed, we cannot exclude the hypothesis that RAF inhibitors could promote cell transformation and/or proliferation in these wtBRAF cells with RAS activation and lead to internal tumors.…”
Section: A B C D E F G H Discussionmentioning
confidence: 86%
“…Thus, it is possible that KRAS codon 12 GAT mutant cells within a tumor appear normal. The fact that KRAS codon 12 mutations have been observed frequently in normal tumor adjacent epithelia, which may or may not be the same KRAS mutation present in the lung adenocarcinoma cells, may provide additional support for this idea [60]. If true, this has clinical significance, because analyzing microdissected tumor samples by DNA sequencing (rather than considering a larger tumor sample using a high-sensitivity method) could potentially decrease the likelihood of KRAS mutation detection in clinical samples.…”
Section: Discussionmentioning
confidence: 99%